2020
DOI: 10.1136/injuryprev-2019-043347
|View full text |Cite
|
Sign up to set email alerts
|

Falls in older aged adults in 22 European countries: incidence, mortality and burden of disease from 1990 to 2017

Abstract: IntroductionFalls in older aged adults are an important public health problem. Insight into differences in fall-related injury rates between countries can serve as important input for identifying and evaluating prevention strategies. The objectives of this study were to compare Global Burden of Disease (GBD) 2017 estimates on incidence, mortality and disability-adjusted life years (DALYs) due to fall-related injury in older adults across 22 countries in the Western European region and to examine changes over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 24 publications
1
73
0
2
Order By: Relevance
“…In males the average is 48 mLO 2 /kg/min and in women 38 mLO 2 /kg/min. From 20-80 years of age, it decreases approximately 10-15 % per decade for sedentary men and women, respectively [5,6]. The classical equation for the maximum heart rate (peak rate = 220 -age in years) implies a maximum of about 155 beats/min at age of 65 years.…”
Section: Changes In Physical Fitness With Increasing Agementioning
confidence: 99%
See 1 more Smart Citation
“…In males the average is 48 mLO 2 /kg/min and in women 38 mLO 2 /kg/min. From 20-80 years of age, it decreases approximately 10-15 % per decade for sedentary men and women, respectively [5,6]. The classical equation for the maximum heart rate (peak rate = 220 -age in years) implies a maximum of about 155 beats/min at age of 65 years.…”
Section: Changes In Physical Fitness With Increasing Agementioning
confidence: 99%
“…With increasing longevity, there is only poor evidence to suggest that these extra years can be lived in good health. Based on Global Burden of Disease study, the rate of years lived with disability increased in both men (7,9%) and women (6,5%) between 1990 and 2017 [5]. Yet in population studies great interindividual diversity in health and functioning is observed in all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Falls in elderly people represent a serious public health problem as the main cause of accidental death in this population. The risk of falling increases with age [ 1 , 7 - 9 ]. Each year, approximately one in every three elderly people experiences a serious fall.…”
Section: Introductionmentioning
confidence: 99%
“…From the age of 60 years, however, 30–60% of people fall, resulting in a rate of 0.7–1.6 falls per year for a person in that age group [ 3 ]. In an aging society, this has extensive consequences not only for the individual but also on a socioeconomic level [ 4 , 5 ]. Falls of older people lead to high expenses for government and health insurance companies, and an increased workload for nurses, relatives, friends, or neighbors.…”
Section: Introductionmentioning
confidence: 99%